2017
DOI: 10.3389/fchem.2017.00043
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides Curbing Soil Fertility: Effect of Complexation of Free Metal Ions

Abstract: Researchers have suggested that the reason behind infertility is pernicious effect of broad spectrum pesticides on non target, beneficial microorganism of soil. Here, studying the chelating effect of selective organophosphate and carbamate pesticides with essential metal ions, at all possible combinations of three different pH (4 ± 0.05, 7 ± 0.05 and 9 ± 0.05) and three different temperatures (15 ± 0.5°C, 30 ± 0.5°C and 45 ± 0.5°C), shows very fast rate of reaction which further increases with increase of pH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 46 publications
1
39
0
1
Order By: Relevance
“…These studies are applicable to all the molecules containing secondary amine [60][61][62][63]. After the derivatization, UV-visible analysis can be used to detect these molecules from various compartments of the environment [54][55][56][57][58][59][60][61][62][63]. In our recent study, we have found that acephate and glyphosate were detectable by UV-visible, FTIR, mass and NMR studies [60,63].…”
Section: Environmental Applicabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…These studies are applicable to all the molecules containing secondary amine [60][61][62][63]. After the derivatization, UV-visible analysis can be used to detect these molecules from various compartments of the environment [54][55][56][57][58][59][60][61][62][63]. In our recent study, we have found that acephate and glyphosate were detectable by UV-visible, FTIR, mass and NMR studies [60,63].…”
Section: Environmental Applicabilitymentioning
confidence: 99%
“…These studies are very important, especially with environmental concern and real-world analysis applications. For example, the detection of glyphosate by UV-visible spectrophotometric methods which are reliable and belongs to real-time analysis, interactions of pesticides with the soils and their adsorption on clay and humates [41][42][43][44][45][46][47][48][49][50][54][55][56][57][58][59][60][61][62][63]. These studies are the foundation of detection of various contaminants and their metabolites through the chromatographic methods in water, soils, fruits, crops, vegetables and other samples [41][42][43][44][45][46][50][51][52][53][54][55][56]64].…”
Section: Environmental Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of trade-offs (Rodríguez et al 2006, Queiroz et al 2015 among ecosystem services are the services soil fertility and production of food and forage provided by arable fields, meadows, and pastures. The stakeholders considered soil fertility necessary for food and forage production, but an increase of the provisioning services may lead to a decrease in soil fertility because of the increased use of fertilizer or pesticides (Fixen et al 2015, Kaur et al 2017.…”
Section: Cognitive Archetypesmentioning
confidence: 99%
“…In relation to its interaction with proteins, it has been observed that the SA and its derivatives possess low to medium covalent interaction with proteins like human serum albumin (HSA) and bovine serum albumin (BSA) (Kumar et al 2015a; Yin et al 2007 andLi et al 2011), that is known to be one of the most abundant proteins in blood and cerebrospinal fluid, playing a fundamental role in the distribution of essential transition metal ions across different parts of the human body. The use of metal complexes as drugs requires transportation of the metal ion in the body which is achieved by the formation of non-covalent coordination of the drugs with its targeted protein, particularly utilizing the amino acid side chains (Archibald et al 2013, Kaur et al 2017).…”
Section: Introductionmentioning
confidence: 99%